Heat stress and orthostatic tolerance - Fumio Yamazaki (Japanese Society of Physical Fitness and Sports Medicine, 2012)
In healthy individuals, exercise and nonexercise (i.e. passive body heating) heat stress induces vulnerability in the cardiovascular system, and is apt to cause hypotension during upright posture, resulting in a reduction of orthostatic tolerance. Reduced orthostatic tolerance is linked to multiple physiological mechanisms including 1) a redistribution of blood flow from central parts of the body to skin, 2) an increase in leg venous compliance, 3) altered baroreflex function, 4) an attenuated venoarterial response in the lower extremities, and 5) a decrease in plasma volume. A combination of countermeasures such as cooling of the body, rehydration, and heat acclimation, can improve orthostatic tolerance in a hot environment. The purpose of this review was to summarize findings investigating the causes of and preventive approaches to heat stress-induced orthostatic intolerance.